Nutritional quality of donkey milk during the lactation - Živkov-Baloš Milica; Popov Nenad; Vidaković-Knežević Suzana; Savić Sara; Gajdov Vladimir; Jakšić Sandra; Ljubojević-Pelić Dragana (Biotechnology in Animal Husbandry)
The Domestic Balkan and Banat donkey (Equus asinus asinus) are native donkey breeds primarily raised in the Special Nature Reserve 'Zasavica', Serbia. The study's objective was to analyze the composition of donkey's milk during the lactation period (12th to 30th week of lactation), regardless of the donkey's breed. The investigated donkey milk composition is characterized by a low content of dry matter, protein and fat and a high amount of lactose, compared to the milk of other dairy animals. The study revealed that content of dry matter ranged from 7.20 to 9.52%, fat ranged from 0.10 to 1.00%, protein ranged from 1.17 to 2.07%, lactose ranged from 4.52 to 6.71%, ash ranged from 0.28 to 0.50% and pH ranged from 6.82 to 7.46. Dry matter, fat, and ash content progressively lowered during lactation, with some oscillations. Milk protein and lactose content were not affected during the lactation stage. The pH value increased progressively during lactation with slight oscillations during the 18th and 21st week of lactation. Statistically significant differences between lactation weeks were established only for lactose content and pH values.